Portable rapid detection of maize chlorotic mottle virus using RT-RAA/CRISPR-Cas12a based lateral flow assay - Lei, Rong; Kuang, Ruirui; Peng, Xuanzi; Jiao, Zhiyuan; Zhao, Zhenxing; Cong, Haolong; Fan, Zaifeng; Zhang, Yongjiang (Frontiers in Plant Science, 2023)
Maize lethal necrosis seriously threatens maize production worldwide, which was caused by coinfection by maize chlorotic mottle virus (MCMV) and a potyvirid. To effectively control maize lethal necrosis, it is vital to develop a rapid, sensitive, and specific detection method for the early diagnosis of MCMV in host plant tissues. Herein, we established a rapid detection procedure by combining the one-step reverse-transcription recombinase-aided amplification (one-step RT-RAA) and CRISPR/Cas12a-based lateral flow assay, which can detect 2.5 copies of the coat protein (CP) gene of MCMV, with 0.96 pg of the total RNA extracted from MCMV infected maize leaves. To make the method more feasible for the field detection, crude virus extraction of plant RNA integrated with one-tube RT-RAA/CRISPR-Cas12a reaction and lateral flow assay, which were implemented on a portable metal incubator at 37~42C with about 1h. This combined detection method presents rapidness, robustness and on-site features in detecting viral RNA, and is a promising tool for the field application in remote areas.